On the Implications of Introducing Cross-Border Loss-Offset in the European Union - Zarko Kalamov; Marco Runkel (Center for Economic Studies and ifo Institute (CESifo), 2015)
This article investigates a tax competition model where countries compete for capital and profits of multinational enterprises (MNEs) through statutory tax rates and cross-border loss-offset provisions, which allow a transfer of foreign subsidiaries' losses to the parent company. A joint implementation of full cross-border loss-relief is welfare maximizing, because it ensures production efficiency and no profit shifting in equilibrium. Local governments choose zero level of the loss-relief in a noncooperative equilibrium, if only capital is mobile and relax the loss-offset, when MNEs engage in profit shifting. Therefore, allowing multinationals to undertake international tax planning activities may be welfare-improving in our model.
Keywords: H32; F23; 330; cross-border loss-offset; tax competition; profit shifting